RESILIENCE ASSESSMENT OF COMMUNAL WATER SUPPLY BASED ON USER PREFERENCE FOR PASIGALAâS POST DISASTER TEMPORARY HOUSING - Wahyu Pramono, Beny
A big archipelago country, having highly prone to a disaster caused by the ring of fire and meeting points of three tectonic plates, stimulating various seismic disasters, is Indonesia's character. In order to mitigate these problems, the Government of Indonesia has passed Law No. 24/2007 concerning disaster mitigation containing a mission to enhance resilience. However, in terms of resilience, especially for the water supply sector, uncomplete technical regulation becomes a primary constraint, resulting in no clear technical framework to monitor, evaluate, and develop a communal system utilized by post-disaster temporary housing for providing water service. Fortunately, the assessment based on the TOSE approach containing the dimension of technic, organization, social, and economy can become an alternative solution to measuring the communal water supply system to deal with extreme events, including seismic disaster. This study evaluates the framework's application based on user preference through the TOSE approach in terms of communal water supply. It also identifies the critical factors affecting the communal water supply resilience in post-disaster temporary housing sites in the Region of Pasigala. Although this study does not show a significant relationship between resilience based on the TOSE approach and the dynamic of water functionality during a disaster as the primary measurement for water resilience according to conventional study, it indicates that environmental condition and the safety toward domestic crime becomes critical factors of water supply resilience in Pasigala's post-disaster temporary housing sites. Besides, this study shows that the mean of household income and the duration of reserve electricity have a considerable relationship with robustness, and the quick access to air or financial service influence significantly toward rapidity through a high score of correlation analysis. Furthermore, the study's result provides the recommendation to put environmental conditions as a priority when the stakeholder establishes the post-disaster temporary housing facility. Besides, it suggests the government to consider several essential factors with the aims of minimizing the risk and accelerating the recovery process regarding the water supply system in post-disaster temporary housing sites.